PROSPECTIVE ANALYSIS DATA OF FLOW AND FORECASTING OF MAXILLOFACIAL PHLEGMON IN VARIOUS MEDICAL-GEOGRAPHIC CONDITIONS - H.P. Ruzyn; Y.O. Pokhodenko-Chudakova; S.N. Hryhorov; E.N. Vakulenko; V. O. Krainia (Ukrainian Medical Stomatological Academy, 2016)
The article describes the possibilities of predicting the results of acute inflammatory processes of maxillofacial area with the use of computer-multifactorial analysis program "Prognosis". The problem of acute inflammatory processes of maxillofacial area in Ukraine and other countries today is characterized by a high prevalence of inefficient treatment, the complexity of timely diagnosis and even mortality. Within the framework of the cooperation agreement between the Department of Surgical Dentistry and Maxillofacial Surgery KhNMU and the Department of Surgical Dentistry of Belarusian State Medical University, used the program "Prognosis" in the clinic and compared the most informative data of these diseases. Submissions from the department of surgical dentistry of the Belarusian State University (Minsk) were processed by our proposed program "Prognosis". In addition to classical methods of diagnosis, such as inspection, palpation, percussion, puncture, and other, currently for the diagnosis of phlegmons applies only limited types of modern methods of diagnostics. We created and offered a program for prognosis. Using the capabilities of the desirability function of acute purulent inflammation of soft tissues program allows timely identification of patients with potentially adverse results, select the optimal treatment regimen, not allowing preventing the development of complications, but also reducing the time of hospital stay and improving outcomes. Therefore, the aim of the work was the comparison of informative data on forecasting and abscesses within the maxillofacial area as an example of a prospective study of these parameters in patients with phlegmons in clinics of Kharkov (Ukraine) and Minsk (Republic of Belarus) for the period January-November 2015. The results of a prospective study material for the period January-November 2015 showed that the percentage of patients with a particular phlegmons localization of the total number of hospitalized patients ranged from 28 to 36% (Kharkov), and 20-28% - in Minsk. It was carried out in a specific chronological sequence. It consists in the following: admission of the patient to the hospital, making all the necessary data and subjecting to computer processing and, depending on the results obtaining express forecast and the correction of the treatment regimen. If necessary, during the treatment re-use program was carried out in the form of so-called current forecast. A comparative analysis of the evaluation of prediction in patients of Kharkiv Regional Hospital and the Minsk Regional Hospital was done. Research has shown, results are reliable and comparable in two different clinics, regardless medical and geographical conditions, which allow recommending it for use in a prospective study of various clinics, independently of each other.